Aerobic exercise increases irisin serum levels and improves depression and fatigue in patients with relapsing remitting multiple sclerosis: A randomized controlled trial - Bilek, Furkan; Cetisli-Korkmaz, Nilufer; Ercan, Zubeyde; Deniz, Gulnihal; Demir, Caner Feyzi (Elsevier Sci Ltd, 2022)
Background: Multiple sclerosis (MS) is a chronic progressive neurodegenerative disease of the central nervous system. Although there is increasing evidence that aerobic exercise has a positive effect on both cognitive and psychological functioning, there is limited evidence for Relapsing-Remitting MS (RRMS) patients. Moreover, it is unclear at what exercise modality and intensity the irisin, the cleaved and circulating form of the exerciseassociated membrane protein Fibronectin Type III Domain Containing 5, is induced in patients with MS. This study aimed to investigate the effect of a regular aerobic exercise program on irisin serum level, depression, fatigue, and cognitive performance in patients with MS. Methods: Thirty-two individuals with RRMS were randomized into 2 groups as control and study groups (mean EDSS score 1.69 and 1.97, respectively). While the Study Group received a combined exercise training consisting of three sessions of aerobic exercise and Frenkel Coordination Exercises per week for 6 weeks, the Control Group received only Frenkel Coordination Exercise training. Before and after the study, the cognitive performance of the participants were evaluated with the Paced Auditory Serial Addition Test with 3-second stimulus (PASAT-3), their maximum aerobic capacity with the Fitmate Pro (R) (VO2max), their fatigue status with the Fatigue Impact Scale (FIS), and their depression status with the Beck Depression Inventory (BDI). Irisin serum levels were analyzed with Enzyme-Linked ImmunoSorbent Assay (ELISA) test from the serum samples of individuals. Results: Our results revealed that the irisin serum level significantly increased in the Study Group. Significant improvement in aerobic capacity, PASAT-3, FIS, and BDI values was observed in the Study Group compared to the Control Group. When the Delta Irisin, Delta VO2max, Delta FIS, and Delta BDI values between the groups were compared, a significant difference was found in favor of the study group. Conclusion: The aerobic exercise revealed significant changes in depression, fatigue and irisin serum levels in MS patients. We think that this study, in which a significant increase in irisin serum level, significant improvement in depression, cognitive performance and fatigue states were obtained in the Study Group, will be a pioneering study for the future studies aiming to investigate the effects of irisin serum level on these symptoms in detail.
Keywords: Aerobic exercise; Irisin; Cognitive; Fatigue; Depression